1974
DOI: 10.1177/00220345740530041201
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Method of Testing on Dentifrice Abrasiveness

Abstract: A method has been developed for testing dentifrice abrasiveness which is based on a commercial toothbrush motor that operates a brush with only one or two tufts and on the application of dentifrice to a disk of neutron-irradiated dentin. Greater precision was found when only one tuft was used. The wear by two commercial dentifrices depended on the force on the brush and on the concentration during testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It is clearly apparent that not only is the abrasive relevant to wear of dentine but also the detergent both interacting to produce variable amounts of wear dependent on which combination is used. Other work has also clearly shown that the dilution of the abrasive in the diluent effects abrasion by different abrasives (Manly et al 1974, Harte & Manly 1976). This was not tested here as an attempt was made to mimic concentration of both abrasive and detergents in common use.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is clearly apparent that not only is the abrasive relevant to wear of dentine but also the detergent both interacting to produce variable amounts of wear dependent on which combination is used. Other work has also clearly shown that the dilution of the abrasive in the diluent effects abrasion by different abrasives (Manly et al 1974, Harte & Manly 1976). This was not tested here as an attempt was made to mimic concentration of both abrasive and detergents in common use.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, the two anionic detergents were the most aggressive and it is known that SLS and therefore probably Adinol are rapidly adsorbed onto hydroxyapatite (Barkvoll et al 1988). There have been several studies on dentine wear with whole toothpaste formulations (Stookey & Muhler 1968, Council on Dental Therapeutics 1970) and a few measuring the influence of diluents, including SLS, on the action of abrasives (Manly et al 1974, Harte & Manly 1975, 1976, Redmalm 1986). Unfortunately, this appears to be the only study that measured the effects of detergents alone on dentine.…”
Section: Discussionmentioning
confidence: 99%
“…The surface profile technique may be more sensitive in detecting differences between toothpastes. The work of Manly & Foster (1967) and Manly et al (1974) on the abrasivity/concentration relationship and that of Davis (1975) on irradiation damage, suggest two sources of differences in the data:…”
Section: Discussionmentioning
confidence: 99%
“…The use of a single tuft also permits the dentifrice slurry to be kept small, permitting the whole sample to be counted, rather than a small fraction. 23 Four different brushes were selected to be representative of hand brushes rather than machine brushes. Brushes A and B were the lhard and medium variety of one brandf of common toothbrush; bruslhes C and D were the hard and medium variety of a different brandg as shown in the illustration.…”
mentioning
confidence: 99%